Is Business Practice of Fair Trade Branding Deceiving Customers? : Case of Malaysia - Mat Zain, Juziana (2014)
Fair trade is a common business practice, which is based on the need to benefit the producers of various retail products. Fair trade branding which characterize products that are certified to be compliant with the principles of fair trade has led to significant ethical implications on the marketing of these products. This study is purposed at finding out if fair trade is deceptive to the consumers or not.